2000
DOI: 10.3184/030823400103167219
|View full text |Cite
|
Sign up to set email alerts
|

Semi-synthesis of triterpene A-ring derivatives from oleanolic and maslinic acids. Part II. Theoretical and experimental 13C chemical shifts

Abstract: Maslinic acid was obtained from olive-pressing residues, and several derivatives were formed. Rearrangements of 2-tosyloxy-derivatives of methyl maslinate made out by acetolysis. The main product of these rearrangements contained a cyclopentanic A-ring as a result of a concerted 2(3) → 4-abeo rearrangement process. Experimental and theoretical (GIAO, B3LYP/6-31G*//MM+) 13C NMR chemical shifts for 20 compounds are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…These data compared with those reported in literature [ 3 ]. Spectra in Figure 2 are given in the supporting information.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…These data compared with those reported in literature [ 3 ]. Spectra in Figure 2 are given in the supporting information.…”
Section: Resultssupporting
confidence: 53%
“…The present study was designed to evaluate whether Syzigium aromaticum -derived triterpenes, OA and MA reduce postprandial glucose in STZ-induced diabetic rats loaded with carbohydrates via inhibition of carbohydrate hydrolysis and reduction of glucose transporters in the gastrointestinal tract. The structures of OA and MA were elucidated by 1 H and 13 C NMR spectral data compared with previously reported values [ 3 , 20 ]. We have previously reported that the hypoglycaemic properties may arise, in part, from the inhibition of glucose transport across the small intestine [ 12 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous works have dealt with the reactivity and rearrangement of different derivatives of oleanolic and maslinic acids, reactions which have provided high yields of several interesting 3(4)→5- abeo and 2(3)→4- abeo products. Recently, our group reported the semisynthesis, theoretical calculations, and biotransformation of cyclic sulfites of polyhydroxylated eudesmanes, showing that the sulfites and sulfates are appropriate intermediates for performing experimental and theoretical studies and, therefore, for preparing other synthons for fine organic synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical methods of substantial quality can be used to calculate NMR data using the gauge-invariant atomic orbital (GIAO) method, yielding data comparable to those of the experiments, , and helping in the assignment of chemical shifts for natural product derivatives. In this sense, the density functional theory (DFT) methods are especially suitable for a wide range of medium- to large-sized molecules.…”
Section: Introductionmentioning
confidence: 99%